1976
DOI: 10.1063/1.432930
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of O(1D) rate constants for reactions with O2, N2, CO2, O3, and H2O

Abstract: Absolute rate constants and their temperature dependencies for the deactivation of O(1D) by five important atmospheric gases are reported. O(1D) atoms are produced by photolysis of ozone at 266 nm and the atoms are directly observed in time resolved decay of the O(1D) →O(3P) radiation at 630 nm. Gases which only quench O(1D) (O2, N2, and CO2) are observed to have a small negative temperature dependence while O3 and H2O, which also have a reactive channel, display no temperature dependence. Arrhenius expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(88 citation statements)
references
References 24 publications
7
80
0
1
Order By: Relevance
“…The predicted value of c given by Tully (1974) agrees with the experimental results of Streit et al (1976). Although there is considerable uncertainty in the theoretical results, they suggest that the amount of energy channeled into N 2 vibration can be an average of 30 AE 10% of the 1.97-eV exothermicity of quenching.…”
Section: Energy Balance Equations For Ions and Electronssupporting
confidence: 79%
See 1 more Smart Citation
“…The predicted value of c given by Tully (1974) agrees with the experimental results of Streit et al (1976). Although there is considerable uncertainty in the theoretical results, they suggest that the amount of energy channeled into N 2 vibration can be an average of 30 AE 10% of the 1.97-eV exothermicity of quenching.…”
Section: Energy Balance Equations For Ions and Electronssupporting
confidence: 79%
“…Streit et al (1976) reported that the measured rate coe cient c j c j . Tully (1974) developed a classic collision complex model to describe production of N 2 j in these reactions.…”
Section: Energy Balance Equations For Ions and Electronsmentioning
confidence: 99%
“…where is the production rate (Streit et al, 1976), u 3 2X5 Á 10 À12 cm 3 s À1 is the rate coecient for quenching of O 1 D by atomic oxygen (Sobral et al, 1993). In the SAR arc region, O 1 D are produced mainly by excitation of O 3 P by thermal electron impact (Kozyra et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, energy transfer from O( 1 D) to O 2 leads to the formation of electronicallyvibrationally excited molecules O 2 (b 1 + g , v) (Streit et al, 1976;Lee and Slanger, 1978). Mlynczak et al (1993) supposed that vibrational kinetics can be neglected, which is possible only if the processes of vibrational-vibrational (V-V) and vibrational-translational (V-T) energy transfer between vibrational sublevels of electronic states are much faster than collisional deactivation of electronically excited states.…”
Section: Introductionmentioning
confidence: 99%
“…O 2 +hν(SRC)→O( 3 P)+O( 1 D) 2.60×10 −6 1.0 Rodrigo et al (1986), DeMore et al (1997) O 2 +hν(Lyman-α)→O( 3 P)+O( 1 D) 3.40×10 −9 0.48-0.58 Rodrigo et al (1986), Reddmann and Uhl (2003) O 3 +hν→O 2 (X, v=0-35 Streit et al (1976), Lee and Slanger (1978), Green et al (2000) O ( …”
Section: Introductionmentioning
confidence: 99%